The Initial Velocity of a Metal Plate Explosively-Launched from an Open-Faced Sandwich (OFS) - WŁODARCZYK, Edward; FIKUS, Bartosz (Engineering Transactions, 2016)
Using analytic solutions for one – dimensional plane boundary value problems related to the launching of solids by detonation products (DPs) of high explosives, algebraic formulae which define the displacement and velocity of a metal plate launched by expanding DP from an open-faced sandwich (OFS) are derived. In addition, the variations of the mechanical parameters of displacement, velocity and density versus the Lagrangian coordinate of expanding DP gases during the launching of the metal plate from the OFS are defined. Variations of these mechanical parameters are also described by algebraic formulae. From analysis of the obtained results, it follows that Gurney’s assumptions of the linear velocity profile of constant – density DP gases significantly deviates from conventional theory of gas dynamics. Gurney’s assumptions introduce a serious error of estimated metal plate velocity (about several dozen percent).